Impact of Reactive Power Compensation on Voltage Profile in Renewable-Integrated Distribution Network - Anuar, Aminudin; Wan Azli, Wan Muhamad Afnan; Wooi, Chin-Leong (Advanced and Sustainable Technologies (ASET), 2026)
The increasing integration of renewable energy sources, especially solar photovoltaic (PV) systems, poses challenges such as voltage fluctuations and power quality issues in modern power networks. Reactive power support has become an effective solution to enhance voltage stability and minimize system losses. This study investigates the impact of reactive power compensation on the IEEE 14-bus distribution system using ETAP software. The system is modified to include solar PV units at selected buses, and 150 kVAR capacitor banks are optimally placed to provide reactive power support. Load flow analysis and the Voltage Deviation Index (VDI) are used to assess performance improvements. Simulation results show that optimal capacitor placement significantly improves voltage profiles, with all bus voltages maintained within the acceptable range of 0.95 p.u. to 1.05 p.u., while reducing active power losses. The findings highlight the importance of reactive power management to ensure the reliable and efficient operation of distribution networks with high penetration of renewable energy sources, and they align with SDG 7 (Affordable and Clean Energy).